Design of a power-saving strategy for a collaborative wireless sensor network of multi-core embedded systems - Céspedes-Deliyore, Randy Steven (2022)
Proyecto de Graduación (Maestría en Electrónica), Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2022.